Jugoslavenski pomorski saobraćaj nakon 1992. godine - Delibašić, Tatjana (Promet - Traffic&Transportation, 2012)
This paper deals with respective data on the fleet of vessels of the EC member states and Yugoslavia including the structure and tonnage as well as the effectuated volumes in cargo transport and development trends. The author pleads for the Adriatic Orientation with particular reference to as close as possible cooperation with the corresponding institution in the EC.